THE EFFECT OF SELLING PRICE AND PRODUCTION COSTS ON CORN FARMERS INCOME IN SEMANDING, KAWEDUSAN VILLAGE, PONGGOK SUB-DISTRICT - Anggun Ma’rifatun Nisa; Hery Suprayitno (Universitas Islam Balitar, 2020)
The purpose of the research is to find out whether there is an influence between selling prices and production costs to the income earned by corn farmers in Semanding Village, Ponggok Sub-District, Blitar Regency. This research is field research and used quantitative methods. The population and sample used are corn farmers in Semanding, Kawedusan Village, Ponggok Sub-District, Blitar Regency as 17 people. Data collection techniques in this research used a questionnaire, and literature study. The data analysis techniques used are descriptive respondents, validity, reliability, classic assumption tests, multiple linear regression tests, coefficient determination tests (R2), correlation tests, and hypothesis testing. The final results showed the selling price partially had a positive and significant effect on income, the production cost had a partially positive and significant effect on income, and the selling price and production costs simultaneously had a positive and significant effect on the income received by corn farmers in Semanding, Ponggok Sub-District, Blitar.